Inovasi Desain Kemasan Alifa Bakery berdasarkan Kaidah Fikih Muamalah di Desa Teluk Pinang - Yahya, Muhammad; Yanto, Riado (Neolectura, 2024)
This research discusses the innovation of Alifa Bakery’s packaging design based on the rules of Fiqh Muamalah in Teluk Pinang Village. The problems that arise in this study by providing a logo image in muamalah packaging this is done to give identity to the bread product. The purpose of this research is to create new packaging that is not only visually appealing but also reflects muamalah values that are in accordance with the social and cultural context of the local comunity. The research method used is descriptive qualitative with data collection techniques through observation, interviews, documentation and literature studies. The results of this study indicate that Alifa Bakery's packaging design innovation based on Fiqh Muamalah rules is able to create significant added value. The designed packaging reflects transparency, honesty, and ethics in business, which is an effort to strengthen consumer confidence in products and brands and become a means of creating a positive impact in business and society in the contemporary era. In addition, this research shows that packaging design innovation can also improve product competitiveness in the market by highlighting muamalah values that are relevant to consumers and local culture. Thus, this research provides added value for producers in developing such micro-enterprises that focus on muamalah values and economic, social, and cultural aspects.